Restoring Motor Functions in Paralyzed Limbs through Intraspinal Multielectrode Microstimulation Using Fuzzy Logic Control and Lag Compensator - Amir Roshani; Abbas Erfanian (Basic and Clinical Neuroscience, 2013)
In this paper, a control strategy is proposed for control of ankle movement on animals using intraspinal microstimulation (ISMS). The proposed method is based on fuzzy logic control. Fuzzy logic control is a methodology of intelligent control that mimics human decision-making process. This type of control method can be very useful for the complex uncertain systems that their mathematical model is unknown. To increase the stability and speed of the system’s response and reduce the steady-state error, we combine the FLC with a lead (lag) compensator. The experiments are conducted on .ve rats. Microelectrodes are implanted into the spinal cord to provide selective stimulation of plantar.exor and dorsi.exor. The results show that motor functions can be restored using ISMS. Despite the complexity of the spinal neuronal networks and simplicity of the proposed control strategy, our results show that the proposed strategy can provide acceptable tracking control with fast convergence.